With a little help from the miners: distributed ledger technology and market disintermediation. Issue 3 (9th April 2018) - Zamani, Efpraxia D.; Giaglis, George M.
Abstract : Purpose: The purpose of this paper is to argue for the role of the blockchain, i.e., distributed ledger technology, in building innovative business models, including machine money, autonomous economic agents and decentralised organisations. Design/methodology/approach: The paper is conceptual/argumentative. As such, it draws on research on (e-)commerce, theories of markets, disruptive innovation and extant studies and conceptual work at the intersection of cryptocurrencies, machine-to-machine commerce and the Internet of Things. Findings: The authors highlight three application areas for blockchains, whereby they can function as applications, can help develop autonomous economic agents and can lead the development of decentralised autonomous organisations. With regards to the question of market disintermediation, the authors suggest that, rather than complete disintermediation, the most probable scenario is that of new types of intermediaries finding previously unthinkable roles to play in mediating blockchain-based economic transactions. With regards to the inhibitors that slow down the technology's adoption and, therefore, the development of new business applications, the authors posit that these relate mainly to the inherent risk of the technology, infrastructure requirements, scepticism of early decision makers and the lack of required new skills and competencies. Originality/value: The authors examine how new forms of digital money and technologies embedding trust in decentralised networks will alter markets and commerce, at a time when many regulatory issues remain unresolved; in doing so, the authors focus on how blockchain-enabled technologies can be used to enable and further develop decentralised trusted peer-to-peer transaction ledger systems and applications and lead to sustainable business models.